Modernization of Islamic Religious Education Mahmud Yunus - Hanifah Oktikasari; Rustam Ibrahim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Education is a key pillar in creating a nation's progress and prosperity. In Islam, education not only develops knowledge but also shapes character and good morals. Since its inception in Indonesia, Islamic education has played a significant role in the process of Islamization, yet it has faced the challenge of remaining relevant to current developments. Mahmud Yunus, a key figure in the reform of Islamic education in Indonesia, made significant contributions to integrating religious and general knowledge into the education system. His thinking emphasized the importance of a curriculum that combines religious and scientific knowledge, the use of Indonesian in learning, and the development of more modern teaching methods. Mahmud Yunus also proposed reforms in Islamic educational institutions, introducing a classical system and a structured curriculum, and emphasizing the role of educators as role models. His reform efforts formed the basis for the development of a more dynamic and adaptive Islamic education to the changing times, making it relevant today.